Wanda Maximoff’s Grieving Process and Her Imaginary World in WandaVision Series: A Lacanian Perspective - Davita Soimatul Fauziah; Ali Mustofa (Universitas Negeri Makassar, 2022)
Abstract. This study aimed at investigating further stages experienced by someone who is going through the process of grieving from the loss of a loved one forever, namely Wanda Maximoff and its relation with her world of her imagination in Matt Shakman's